2019
DOI: 10.1093/eurpub/ckz186.486
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders among university students: a public health challenge. An European study

Abstract: Background Eating disorders (ED) and behavioural risk factors among students in higher education remain to be investigated. The aim of the study was to identify the prevalence of ED and the behavioural factors associated with ED in university students in four European universities: Chisinau (Ch) in Republic of Moldava, Cluj-Napoca (CN) in Romania, Miskolc (Ms) in Hungary and Rouen (R) in France. Methods In the four countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Details of the studies included are shown in Table 2 . Of the 89 studies only two (2.2%) were grey literature: [ 117 ] and [ 121 ]. They were of a similar quality compared to the published studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the studies included are shown in Table 2 . Of the 89 studies only two (2.2%) were grey literature: [ 117 ] and [ 121 ]. They were of a similar quality compared to the published studies.…”
Section: Resultsmentioning
confidence: 99%
“…Sample Size N = 262. ED Measure: EAT-40 %Female = 59.5%, Age = 21.7 years, BMI = 21.5 kg/m 2 7 46 Ladner (2019) [ 121 ] France Cross-sectional design. Sample Size N = 3076.…”
Section: Resultsmentioning
confidence: 99%
“…The currently available survey data reveal that B.D. is a prevalent alcohol consumption pattern [ 14 ]; less is known about the Romanian student population’s excess drinking habits among males and females correlated with lifestyle factors, such as other risky behaviors, food behaviors, physical activity, and sleep behaviors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%